Nanoparticle preconditioning for enhanced thermal therapies in cancer. (April 2011) - Shenoi, Mithun M; Shah, Neha B; Griffin, Robert J; Vercellotti, Gregory M; Bischof, John C
Nanoparticles show tremendous promise in the safe and effective delivery of molecular adjuvants to enhance local cancer therapy. One important form of local cancer treatment that suffers from local recurrence and distant metastases is thermal therapy. In this article, we review a new concept involving the use of nanoparticle-delivered adjuvants to ''precondition'' or alter the vascular and immunological biology of the tumor to enhance its susceptibility to thermal therapy. To this end, a number of opportunities to combine nanoparticles with vascular and immunologically active agents are reviewed. One specific example of preconditioning involves a gold nanoparticle tagged with a vascular targeting agent (i.e., TNF-αα). This nanoparticle embodiment demonstrates preconditioning through a dramatic reduction in tumor blood flow and induction of vascular damage, which recruits a strong and sustained inflammatory infiltrate in the tumor. The ability of this nanoparticle preconditioning to enhance subsequent heat or cold thermal therapy in a variety of tumor models is reviewed. Finally, the potential for future clinical imaging to judge the extent of preconditioning and thus the optimal timing and extent of combinatorial thermal therapy is discussed.